Pengaruh Corporate Social Responsibility (CSR) terhadap Kinerja Keuangan pada Perusahaan Sektor Consumer Non-Cylicals dan Basic Material - Desdi Romawati Aritonang; Liana Rahardja (STIE-JIC, 2022)
This study aimed to examine the influence of corporate social responsibility (CSR) activity disclosure on the financial performance of Consumer Non-Cyclical and Basic Material sector companies registered in IDX from 2015-2019. Financial performance was measured using Return on Asset, Return on Equity, and Net Profit Margin, as well as sales growth, size, and leverage as control variables. The population comprised 123 companies of Consumer Non-Cyclical and Basic Materials. This study used the purposive sampling method appropriate to the predetermined criteria to select 39 companies within 5 years, resulting in 195 observations. The data obtained from the Indonesia Stock Exchange from 2015 to 2019 were analyzed using multiple linear regression with E-views 9. The results of the first regression partially showed that CSR disclosure positively and significantly influences Return on assets. The second regression partially indicated that CSR disclosure positively and significantly influences Return on Equity. Similarly, the third regression partially showed that CSR disclosure positively and significantly impacts Net Profit Margin. CSR disclosure, Sales Growth, Firm Size, and Leverage significantly affect Return on Asset, Return on Equity, and Net Profit Margin in Consumer Non-Cyclicals and Basic Material sector companies listed in IDX in 2015-2019.